A comparison of voluntary and mandated climate change-related disclosure. Issue 2 (August 2019) - Perera, Luckmika; Jubb, Christine; Gopalan, Sandeep
Abstract: This study draws on legitimacy theory to investigate the relationship between mandatory disclosure of greenhouse gas emissions by companies that are subject to specific environmental legislation (the Australian National Greenhouse Energy Reporting Act 2007) and the level of voluntary environmental disclosures. Using a sample of 535 observations, we find that i) Overall, legislation-affected companies increase their disclosures compared with non-affected companies, ii) As many companies reduce their disclosures as increase them, iii) there is an increase in the level of emissions volume disclosures in legislation-affected companies compared with the same company pre-implementation, iv) legislation-affected higher emitters have higher levels of voluntary disclosures. These findings are consistent with legitimacy theory, which predicts differential disclosures in circumstances to avoid scrutiny.